Promotion of Plant Growth in Arid Zones by Selected Trichoderma spp. Strains with Adaptation Plasticity to Alkaline pH - Juan Pablo Cabral-Miramontes; Vianey Olmedo-Monfil; María Lara-Banda; Efrén Ricardo Zúñiga-Romo; Elva Teresa Aréchiga-Carvajal (Biology, 2022)
Trichoderma species are filamentous fungi that support plant health and confer improved growth, disease resistance, and abiotic stress tolerance. The objective of this study is to describe the physiological characteristics of the abundance and structure of Trichoderma model strains from arid zones and evaluate and describe their possible adaptation and modulation in alkaline pH. The presence of biotic factors such as phytopathogens forces farmers to take more actions such as using pesticides. In addition, factors such as the lack of water worldwide lead to losses in agricultural production. Therefore, the search for biocontrol microorganisms that support drought opens the door to the search for variations in the molecular mechanisms involved in these phenomena. In our case, we isolated 11 tested Trichoderma fungal strains from samples collected both from the rhizosphere and roots from two endemic plants. We probed their molecular markers to obtain their identity and assessed their resistance to alkaline conditions, as well as their response to mycoparasitism, plant growth promotion, and drought stress. The findings were worthy of being analyzed in depth. Three fungal taxa/species were grouped by phylogenetic/phenotypic characteristics; three T. harzianum strains showed outstanding capabilities to adapt to alkalinity stress. They also showed antagonistic activity against three phytopathogenic fungi. Additionally, we provided evidence of significant growth promotion in Sorghum bicolor seedlings under endemic agriculture conditions and a reduction in drought damage with Trichoderma infection. Finally, beneficial fungi adapted to specific ambient niches use various molecular mechanisms to survive and modulate their metabolism.